Sediment sourcing in the Gangetic alluvium, Himalayan Foreland Basin – competition between Himalayan and cratonic hinterland - Sinha, R; Kettanah, Y; Gibling, MR; Tandon, SK; Jain, M; Bhattacharjee, PS; Dasgupta, AS; Ghazanfari, P (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1330 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.149